STUDI LITERATUR: PENGARUH TERAPI PIJAT REFLEKSI KAKI TERHADAP KUALITAS TIDUR LANJUT USIA - Chaerun Nissa; Ashar Prima; Fauziah Hamid Wada; Puji Astuti; Salamah T Batubara (Jurnal Ilmiah Keperawatan IMELDA, 2021)
WHO states that Indonesia's population is the fourth largest population after China, India, and the United States. According to the 2013 World Health Statistics data, the population of China is 1.35 billion, India is 1.24 billion, the United States 313 million, and Indonesia is in fourth place with 242 million WHO population predicts that by 2020 the estimated number of Indonesia's elderly will be around 80,000,000. Cases of insomnia in the elderly are higher than in other age groups, which is 12–39%. One therapy that can overcome sleep disorders in the elderly is foot reflexology massage therapy. This literature review aims to determine the effect of foot reflexology massage in the elderly who experience sleep disorders. The design in this scientific paper is a literature review search using an electronic data base that is google scholar and pubmed. The keywords used in the search are elderly, foot reflexology, sleep of quality. The inclusion criteria used in the article are full text accessible in English and Indonesian, the year of the journal used is limited to the last ten years. The results found 1 article from Google Scholar and 2 articles from PubMed discussing the effectiveness of foot reflexology massage on improving sleep quality in the elderly. Literature review results from the three articles show that foot reflexology is effective in improving sleep quality in the elderly.